Eastern Africa Farmer Innovation Fair - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The Eastern African Farmer Innovation Fair was held on 28th and 29th May 2013 and showcased innovations by smallholder farmers – women and men – giving them public recognition. The event highlighted the importance of farmer innovation in agricultural development, brought policymakers and the general public in Kenya in contact with farmer innovators, and provided an opportunity for the international participants in the Agricultural Innovation Systems (AISA) workshop to meet and engage with the innovators. The fair was hosted by Prolinnova–Kenya and co-organised with the Netherlands-supported AgriProFocus (APF) network, CCAFS and other organizations concerned with smallholder agricultural development. It involved farmer innovators from Ethiopia, Kenya, Tanzania and Uganda. Photos: S. Makau (CCAFS)